A Calculation Method of Bearing Capacity of Single Squeezed Branch Pile Based on Load Transfer Method. (25th February 2022) - Liu, Li; Ma, Hong-wei; Yang, Xiao-li; He, Qing-rui; Yuan, Song
Abstract : A calculation method of the bearing capacity of single squeezed branch pile is established based on the load transfer method. In the method, the hyperbolic model is used to describe the nonlinear load-displacement relationship of pile-soil interaction at the pile tip, the pile skin, and the squeezed branch, and the theoretical expression of six load transfer coefficients of squeezed branch pile is given. The correctness of the method is proved by a small-scale model test in homogeneous soil and a large-scale model test in stratified soil. The results show that the calculation based on the load transfer method is applicable to predict the ultimate load in engineering application.